Police Crisis Communication Strategy in Public Opinion Management Based on Digital Transparency and Institutional Accountability in the Era of Information Disruption - Widya Bhakti Dira; Syafruddin Syafruddin; Kif Aminanto (Indonesian Journal Publisher, 2026)
This study aims to analyze the legal issues of police crisis communication strategies in managing public opinion in the era of information disruption and formulate legal reforms based on digital transparency and institutional accountability to strengthen public trust in law enforcement institutions. The study employs a normative juridical method with a statutory and conceptual approach through an analysis of Law Number 2 of 2002 concerning the Indonesian National Police, the Law on Public Information Disclosure, the Law on Information and Electronic Transactions, Law Number 25 of 2009 concerning Public Services, as well as various public communication regulations and police professional codes of ethics. The study discovers that police crisis communication strategies in Indonesia continue to exhibit both normative and empirical weaknesses, including slow responses to viral issues, inconsistent information among officials, limited digital transparency, suboptimal media monitoring and digital intelligence, and the lack of comprehensive regulations governing law enforcement digital crisis communication. These conditions have led to increased disinformation, trial by social media, and a decline in the legitimacy of police institutions in the community. Therefore, legal reform is needed through the development of an integrated digital crisis governance model, including the establishment of a National Police Crisis Command Center, the implementation of artificial intelligence sentiment analysis, an early warning system, a rapid digital clarification mechanism, and the standardization of national crisis communications based on digital transparency, human rights protection, and due process of law. These legal reforms are expected to create a police public communications system that is adaptive, accountable, humanistic, and responsive to developments in information technology, in order to strengthen public trust, institutional legitimacy, and the effectiveness of law enforcement in Indonesia's digital democracy.